2018
DOI: 10.3389/fnmol.2018.00248
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin Relieves Neuropathic Pain Through GABA Release and Presynaptic TRPV1 Inhibition in Spinal Cord

Abstract: Objective: Oxytocin (OT) is synthesized within the paraventricular nucleus and supraoptic nucleus of the hypothalamus. In addition to its role in uterine contraction, OT plays an important antinociceptive role; however, the underlying molecular mechanisms of antinociceptive role of OT remain elusive. We hypothesized that the antinociceptive effect of OT on neuropathic pain may occur via inhibition of TRPV1 activation in the spinal cord. The present study explores the antinociceptive role of OT and its mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 50 publications
0
50
0
Order By: Relevance
“…Ramirez and others studied the effect of surgical hypophysectomy and the effect on the hypothalamic region, but such findings do not seem to explain how radiosurgery works. The quick-acting effect on pain relief after radiosurgical hypophysectomy goes beyond the eventual tumor response to hormonal alterations and pose even more complex questions as to the likely radiobiological effect of radiosurgery; it also possibly supports the idea of 'radiomodulation,' as the clinical effects are much faster than what is expected of tissue response or ablation to a high dose of radiation [16]. Our center directs the highest isodose towards the neurohypophysis.…”
Section: Discussionmentioning
confidence: 70%
“…Ramirez and others studied the effect of surgical hypophysectomy and the effect on the hypothalamic region, but such findings do not seem to explain how radiosurgery works. The quick-acting effect on pain relief after radiosurgical hypophysectomy goes beyond the eventual tumor response to hormonal alterations and pose even more complex questions as to the likely radiobiological effect of radiosurgery; it also possibly supports the idea of 'radiomodulation,' as the clinical effects are much faster than what is expected of tissue response or ablation to a high dose of radiation [16]. Our center directs the highest isodose towards the neurohypophysis.…”
Section: Discussionmentioning
confidence: 70%
“…In this context, two recent studies (Nersesyan et al, 2017 ; Sun et al, 2018 ) add a new layer to the analgesic mechanisms of the OT, suggesting that apart from the role of OTR and its downstream mechanism, this peptide also interacts (directly or indirectly) with the transient receptor potential vanilloid type1 (TRPV1) at peripheral and spinal levels. Certainly, since this channel physiologically functions as a detector of noxious stimuli (Caterina et al, 2000 ) and appears to be crucial for the transition from acute to chronic pain (Choi et al, 2016 ), there is a strong motivation to develop molecules modulating TRPV1 to treat neuropathic pain.…”
mentioning
confidence: 99%
“…Since OT plays its effects mainly by activating OTRs in the spinal cord (Jiang et al, 2014;Sun et al, 2018), we then confirmed whether spinal OTRs mediate intrathecal OT induced scratching behavior. Selective activating OTRs by its agonist, TGOT or TC OT39 (also an antagonist of V1aR) produced scratching behaviors equivalent to that induced by the same dose of OT, whereas antagonizing OTR by its antagonist, Atosiban attenuated OT-induced scratching behaviors, indicating that OTRs mediates intrathecal OT induced scratching behavior.…”
Section: Discussionmentioning
confidence: 53%
“…This intense and acute scratching behavior is usually masked by the analgesic effect of OT. However, the starting and peak time of these two actions are different: intrathecal OT-induced hindpaw scratching behavior is most obvious within 5 min, whereas the analgesic effect of intrathecal OT is most significant during 20-30 min after injection (Sun et al, 2018). These findings caught our attention.…”
Section: Discussionmentioning
confidence: 92%